2020
DOI: 10.3390/antiox9070580
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Rhoifolin in Scopolamine-Induced Amnesic Zebrafish (Danio rerio) Model

Abstract: Rhoifolin (Rho) exerts many biological activities such as anticancer, antidiabetic, hepatoprotective, antirheumatic, antibacterial, and antiviral properties. The neuroprotective action of this compound has not been studied. The goal of this study was to investigate the improvement impact of Rho on scopolamine (Sco)-induced zebrafish anxiety, amnesia, and brain oxidative stress and to elucidate the underlying mechanisms involved. Zebrafish were treated with Rho (1, 3, and 5 μg/L) for nine consecutive da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 52 publications
5
29
0
Order By: Relevance
“…In Figure 5F, for the carbonylated proteins levels, the one-way ANOVA test showed the following value between groups of animals F(4,45) = 15.92, p = 0.0002. Elevated levels of carbonylated proteins, lipid peroxidation leading to oxidative stress may also be a reason for memory loss through the administration of scopolamine [60]. This is also observed in our evaluation because the group of fish that received the dose of SCOP 100 µM showed a high level of carbonylated proteins compared to the control group (p < 0.01).…”
Section: Pearson Correlations Between Behavioral and Biochemical Parameterssupporting
confidence: 80%
See 1 more Smart Citation
“…In Figure 5F, for the carbonylated proteins levels, the one-way ANOVA test showed the following value between groups of animals F(4,45) = 15.92, p = 0.0002. Elevated levels of carbonylated proteins, lipid peroxidation leading to oxidative stress may also be a reason for memory loss through the administration of scopolamine [60]. This is also observed in our evaluation because the group of fish that received the dose of SCOP 100 µM showed a high level of carbonylated proteins compared to the control group (p < 0.01).…”
Section: Pearson Correlations Between Behavioral and Biochemical Parameterssupporting
confidence: 80%
“…The total distance traveled by the zebrafish inside the new tank reflects the general/motor neurological phenotypes. Zebrafish is sensitive to nonspecific motor deficiencies and sedative effects of drugs such as SCOP [60,61], but IMP given at a dose of 20 mg/L has significantly stopped these effects. The HE greatly prevented the hypolocomotion and memory deficits caused by the SCOP administration, as evidenced by doses of 1 mg/L and 3 mg/L.…”
Section: Effects Of H Erinaceus Extracts On Anxiety In Ntt Taskmentioning
confidence: 99%
“…In a previous study, Zanandrea et al [ 46 ] showed that SCOP administration (100 µM for 1 h) to zebrafish did not alter the specific activity of AChE compared to control fish. In contrast, several other reports have demonstrated that SCOP (100 µM for 30 min) increased the activity of this enzyme in the zebrafish brains [ 36 , 37 , 38 , 92 , 93 ]. Ziani et al [ 41 ] showed that NIC (1 mg/L for 3 min) increases the AChE activity when it is co-administered with a compound that provokes a fear response in zebrafish but not when NIC is administered alone.…”
Section: Resultsmentioning
confidence: 59%
“…The biochemical results obtained in this study indicated that COT and 6HLN exhibit an antioxidant profile in the SCOP-induced zebrafish model of AD. Several reports showed that SCOP treatment induces oxidative stress in the brain of zebrafish [ 36 , 37 , 38 , 92 , 93 ] or rodents [ 64 , 96 , 97 , 98 , 99 ]. In a cell line derived from Danio rerio gill tissue, NIC treatment (3–7 mg/L for 12 h) has been shown to induce intracellular ROS generation in a dose-dependent manner [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation